Evaluasi Perkerasan Jalan Menurut Metode Bina Marga Dan Metode PCI (Pavement Condition Index) Serta Alternatif Penangananya (Studi Kasus:Ruas Jalan Danliris Blulukan-Tohudan Colomadu Karanganyar) - Rondi, Mochamad, Dr.Sri Sunarjono (2016)
The condition evaluation of the road damage is necessary for monitoring the level of destruction occurs on a roads. The results obtained will be helpful in the preparation of the program and budgeting of road handling rehabilitation. Two methods can be used to assess the condition of the pavement damage are Bina Marga method and PCI method ( pavement condition index), this research has the purpose to know the types of damage and compare both methods to know the value of the pavement condition and another alternative ways of handling according to the existing damage on Danliris Blulukan-Tohudan Colomadu Karanganyar roads.This research is done with damage pavement surface visual survey and also LHR survey ( The average daily traffic ) during a day on the roads, after obtained the data from the field then analyzed using the Bina Marga method and PCI method ( pavement condition index).The results obtained from this research is the damage that there is a pothole (2,98%), Patching (0.67%), alligator cracking (1.19%), longitudinal cracking (0.01%), depression (6,63%), raveling (100%) and on the Bina Marga method reachable values priority order (UP) = 3 (inserted in the road improvement program). PCI methods have the result is the value of the levels of damage 2,66 ( way categorized failed ). The results of these have the recommendations of the reconstruction with recycling Cement Treated Recycling Base (CTRB) method.